Respuesta :

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

[tex]2x - 6 + 3 = 6x - 5[/tex]

[tex]2x - 3 = 6x - 5[/tex]

[tex]6x - 5 = 2x - 3[/tex]

Add sides 5

[tex]6x - 5 + 5 = 2x - 3 + 5[/tex]

[tex]6x = 2x + 2[/tex]

Subtract sides 2x

[tex] - 2x + 6x = - 2x + 2x + 2[/tex]

[tex]4x = 2[/tex]

Divide sides by 4

[tex] \frac{4x}{4} = \frac{2}{4} \\ [/tex]

[tex]x = \frac{1}{2} \\ [/tex]

_________________________________

CHECK :

[tex]2( \frac{1}{2} ) - 3 = 6( \frac{1}{2} ) - 5 \\ [/tex]

[tex]1 - 3 = 3 - 5[/tex]

[tex] - 2 = - 2[/tex]

Thus the solution is correct....

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

Ok so if this is basic algebra it should be x=-1

First combine like terms:

you can add 6 and 3 in 2x-6+3

2x-9=6x-5

Second get x alone:

you can add 9 to both sides and get

2x=6x+4

then you can subtract 6 from both sides which would leave you

-4x=4

finally divide -4 from both sides and you get

x=-1

I hope this helps! Have a nice day or night :)